Use of Imported Inputs and the Cost of Importing : Evidence from Developing Countries - Amin, Mohammad; Islam, Asif (World Bank Group, Washington, DC, 2014)
For a representative sample of manufacturing firms in 26 countries, this paper shows that changes in the cost of importing over time are significantly and negatively correlated with changes in the percentage of firms' material inputs that are of foreign origin. Furthermore, the paper shows that there may be a nonlinear relationship between import costs and imports. These findings are important, as recent studies point toward a significant positive effect of imported inputs on productivity and growth. It is hoped that the present paper inspires more work on the determinants of the use of imported inputs, especially in developing countries.